Otimização de infraestrutura de rede de telecomunicações - Covalski, Karina (2012)
Given the technological advances in both hardware and software, and the need to optimize the telecommunications systems, this paper suggests the implementation of a VoIP network to a provider of telephony services. Currently the company uses the system of conventional telephony in PSTN (Public Switched Telephone Network), networks providing voice services through the circuit switched and data services through packet switching. The proposed network converges (integrates data and voice) and aims to increase the capacity of customer service as well as the modernization of telecommunications services. To achieve the proposed objectives, was performed a literature review of the principles of networks and protocols used. Afterwards the identification of contemporary architecture and development of the proposed architecture. At the end was created a comparative analysis. It follows that convergence is part of the plan of competitiveness among companies in the telecommunications industry, enabling the expansion of the number of subscribers as well as the relentless pursuit of value-added services, among these services are the Internet and the TV service, which will be the big difference between companies of the telecommunications industry in the upcoming years.